2019
DOI: 10.3390/nu11050941
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice on Salt and Assessment of Dietary Salt and Fat Intake among University of Sharjah Students

Abstract: Background: Cardiovascular diseases are the main cause of deaths in the United Arab Emirates and reducing dietary salt intake is recommended to improve the population’s health. Methods: a cross-sectional survey was given to 401 students from the University of Sharjah to investigate knowledge, attitudes, and practices related to dietary salt intake and a 24-h dietary recall among a subsample of 122 students, to assess the dietary intake of total fat, cholesterol, saturated fat, trans fat, and sodium. Results: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
5
28
1
Order By: Relevance
“…These findings are similar to the Lebanon study which showed that 60% of the participants used table salt [40]. Likewise, 61% of university students in the UAE reported adding salt while cooking, and 14% of the participants often added salt to food even before tasting it [21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are similar to the Lebanon study which showed that 60% of the participants used table salt [40]. Likewise, 61% of university students in the UAE reported adding salt while cooking, and 14% of the participants often added salt to food even before tasting it [21].…”
Section: Discussionsupporting
confidence: 85%
“…The questionnaire assessed knowledge relating to salt and health outcomes, frequency of consumption and their perceived salt consumption, and was developed according to the WHO/PAHO recommendations for the assessment of population sodium intake and behaviors. The development and performance of the specific questionnaire has been described elsewhere [21].…”
Section: Knowledge Attitude and Practice (Kap) Questionnairementioning
confidence: 99%
“…This could be a main deterrent and a crucial knowledge gap that affect Sri Lanka's efforts to implement the NSRS's aim to reduce population level dietary salt consumption. It was also noted that this finding is compatible with findings of the studies in other LMICs 14, [16][17][18]21 . Furthermore, the indirect estimation of daily dietary salt consumption in our study showed that Sri Lankans consume higher than the daily requirement of salt.…”
Section: Discussionsupporting
confidence: 91%
“…Based on a desk review of published literature on surveys with similar objectives [12][13][14][15][16][17][18] , we developed an interviewer administered multicomponent knowledge, attitude, and practice survey questionnaire on salt and health as an online version using EpiCollect5 free data gathering platform 19 . in the present study, we estimated the approximate amount of per capita dietary salt of the households of adults included in the study by inquiring into the amount of monthly purchases of salt to the households and the number of household members.…”
Section: Study Instrumentmentioning
confidence: 99%
“…Smartphone apps may be effective in supporting people, especially with cardiovascular diseases, to make lower salt food purchases [19]. Culture-specific awareness campaigns on salt intake and its association with health are needed [20].…”
Section: Introductionmentioning
confidence: 99%